Kestabilan Lereng Model Tridatu Berkolaborasi Dengan Hydroseeding Berbasis Masyarakat (Studi Kasus: Desa Songan A dan B Kintamani) - I Made Nada; Ida Bagus Suryatmaja; I Gede Oka Darmayasa (Program Studi Teknik Lingkungan Unmas Denpasar, 2022)
Landslide disaster is one of the events that often occurs on the island of Bali, especially in Songan A and B Kintamani villages as happened on February 9, 2017 which claimed lives. One way ti characterize soil properties is to use geotechnical methods. Five slopes that have the potential for landslides in Songan A Village (dsa1, dsa2) and Songan B Village (dsb1, etc2, etc3) were characterized by physical soil properties such as cohesion, shear angle, density and slope geometry analyzed for slope stability using the Fellenius method manually. This study uses a quantitative approach, to determine the value of the factor of safety factor generated for each existing slope is 1.45, 1.35, 1.36, 1.13, 1.20 for the five slopes (FK < 1.5) if a landslide occurs, the landslide will piled up roads and houses. From the results of the characterization, mitigation is carried out in the form of slope arrangement of the Tri Datu Model in collaboration with community-based Hydroseeding 0.93 and 16.40 m3, 2.34 and 3.18 m3, 1.65 and 9.19 m3, 1.52 and 9.8 m3 all values of the factor of safety of slopes (FK > 1.5).